THE SIGNIFICANT IMPORTANCE OF DATA SCIENCE IN THE ECONOMY (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In the digital age, data science has emerged as a pivotal force driving economic transformation across industries and sectors. This article explores the profound impact of data science on informed decision-making, operational efficiency, innovation, policy formulation, economic opportunities, and global challenges. It emphasizes the importance of ethical considerations in data use and privacy protection amidst the rapid proliferation of data-driven technologies.